Principles of Entrepreneurship (ENT 530): Business model canvas: Adam’s Wonder juice / Adam Haikal Abdul Razak - Abdul Razak, Adam Haikal
Adam’s Wonder juice sells fresh juice drink products for customers, providing variety of fruits and vegetables that helps with health of customers. Our clients are customers who wants to maintain a healthy well-being or even cure certain disease naturally without having to consume chemical-based pharmaceuticals. Our target is anyone who is a health and fitness enthusiast, be it the elders or younger people. Our strategy is to emphasize the freshness and quality of fruit and vegetables juice, without using preservatives, sweetener, or flavouring. So the marketing strategy is to attract more customers that do not like to eat fruit or vegetables. We will change their opinion in a blink of an eye. This time they can consume it with the best of taste at Adam’s Wonderjuice.Also, it is membership based to attract more regular customers to ensure constant money Flow.This Company has only 1 owner, who is also the one and only worker. Instead of partnership, this business use sole proprietorship which makes it less complex in terms of management and delegation of work. Though this company only has 1 store in Malaysia, it is still new and open to any advancement and development in future. We advertise in social media, advertisements, and through colleagues. It’s about time till everybody is reached and the store is widen throughout Malaysia and even international.